Integrated geochemical and biomarker signature of fast-growing Fe-Mn nodules from the Gulf of Finland, Baltic Sea - Shulga, Natalia; Perfilov, Peter; Ryazantsev, Konstantin (Frontiers in Marine Science, 2025)
Ferromanganese (Fe-Mn) nodules, characterized by rapid growth and diverse morphologies, are widespread on the Baltic Sea seafloor. This study provides a comprehensive analysis of the bulk elemental composition, internal structures, and organic matter (OM) characteristics based on n-alkane distributions in Fe-Mn nodules and their underlying sediments from the Gulf of Finland. The investigated nodules are of diagenetic origin and include both Fe-rich and Mn-rich types. The have spheroidal and discoidal morphologies with pronounced concentric layering. The results indicate that the nodules accumulate both terrestrial and bacterially derived OM which undergoes active diagenetic transformation. Regularized Canonical Correlation Analysis (rCCA) applied to this integrated dataset revealed a strong multivariate relationship between organic matter and elemental composition. The analysis of Internal microstructures revealed microglobular, twisted fibrous, and colloform textures, alongside biomorphic features. These textures reflect coupled abiotic and biological mineralization processes. The absence of correlation between nodule morphology, geochemical type, and underlying sediment properties demonstrates that highly localized microenvironments control nodule formation. This study refines the genetic model of shallow-water fast-growing Fe-Mn nodules, highlighting the crucial role of organic matter-driven diagenesis under dynamic redox conditions in ore formation.